Characteristics and formation processes of (Ba, K, NH4)-feldspar and cymrite from a lower Cambrian black shale sequence in Anhui Province, South China. (28th February 2018) - Chang, Chao; Hu, Wen-Xuan; Fu, Qi; Cao, Jian; Wang, Xiao-Lin; Wan, Ye; Yao, Su-Ping
ABSTRACT: Barium-rich silicates were recently found in the lower Cambrian black shale sequence of Anhui Province, South China. The Ba silicates can be divided into Ba-poor K-feldspar, Ba-rich K-feldspar and cymrite, on the basis of occurrence and composition. The Ba-poor K-feldspar have low BaO contents (<1.00 wt.%) and occur as sporadic grains in mudstone. In contrast, the Ba-rich K-feldspar have higher BaO contents (1.36–20.51 wt.%) and occur mainly as rims around grains of Ba-poor K-feldspar in mudstone, as void fillings in dolostone, and as grains dispersed in chert. The cymrite is observed only in chert and occurs as dispersed euhedral tabular crystals. Analyses of the Ba-poor K-feldspar and Ba-rich K-feldspar provide compositions that total <100 wt.% and show non-stoichiometry characterized by (Na + K + Ba + Ca)apfu less than 1.00 and (Al + Si)apfu slightly higher than 4.00. Raman and infrared (IR) spectroscopy has revealed the presence of ${\rm NH}_{\rm 4}^{\rm +} $ and H2 O in the Ba-rich K-feldspar, which accounts for the unusual composition of these feldspars. We suggest that the formation processes of the Ba-poor K-feldspar, Ba-rich K-feldspar and cymrite were closely associated with multi-stage hydrothermal fluids enriched in Ba and NH4, consistent with an extensional tectonic setting during the early Cambrian. The Ba-poor K-feldspars might have formed through interactions between pre-existing K-feldspars and hydrothermal fluids. The Ba-rich K-feldspars in mudstone and dolostone formed mainly by precipitation from hydrothermal fluids that infiltrated the sediments, and we suggest the Ba-rich K-feldspars and cymrite in the chert are of exhalative hydrothermal origin.